Integrating Multiple Intelligences into Daily Plans: A Preschool Example - Gürkan, Tanju; Dinçer, Çağlayan; Çabuk, Burcu (Prof.Dr. Abdullah Kuzu, 2019)
The purpose of this qualitative study was to evaluate the effectiveness of Multiple Intelligences Theory (MI) onpreschool children’s learning styles, interests and active participation to the daily activities. Researchersconducted a two-phased study in an urban preschool classroom of 14 children who are at the age of 6 with thecooperation of the classroom teacher. In the first phase, the teacher made observations of her class to decide thedominant intelligences, learning styles, interests and participation of the children while she was conducting hertraditional semi-structured daily plans based on the National Preschool Education Curriculum. Based on theobservations, for each child, she filled out the MI Inventory (MULIN) developed by the researchers. Then, eachchild was interviewed by one of the researchers and asked to mark the MI Self Evaluation Picture Control List(MISEC) developed by Fleetham (2008). The data collected was graphed and interpreted to conclude the MIProfile of the class. In the second phase, children were exposed to the Daily Plan Enriched with MI Inspirationsin the leadership of the teacher. Researchers observed and videotaped the whole procedure. Then, the teacher wasinterviewed to find out whether there were differences on the children’s interests and active participation duringthe daily plan enriched with MI inspirations comparing with the traditional daily plans she has been conducting.The findings of the study showed that Daily Plan Enriched with MI Inspirations made a positive effect onchildren’s interests and active participation in the daily activities since they covered all the intelligences andaddressed different learning styles of the children. Research findings not only provide insight into the role of MIon preschool children’s interests and active participation but also draw attention to the importance of having allthe eight intelligence and addressing all the learning styles of the children in the daily plans.

Bu nitel araştırmanın amacı, Çoklu Zeka Kuramı’nın okul öncesi dönem çocuklarının öğrenme stilleri, ilgi alanları ve günlük aktivitelere aktif katılımları üzerindeki etkililiğini değerlendirmek olarak belirlenmiştir. Araştırmacılar, sınıfın öğretmeninin işbirliği ile 6 yaşındaki 14 çocuğun şehir içinde yer alan anaokulu sınıfında iki aşamalı bir çalışma yürütmüşlerdir. Birinci aşamada öğretmen, Okul Öncesi Eğitim Programı’na dayanan yarı yapılandırılmış geleneksel günlük planlarını yürütürken, çocukların baskın zekalarına, öğrenme stillerine, ilgi alanlarına ve aktif katılım durumlarına karar vermek amacıyla sınıf gözlemleri yapmıştır. Gözlemlerine dayanarak, her çocuk için, araştırmacılar tarafından geliştirilen Çoklu Zeka Envanteri’ni (MULIN) doldurmuştur. Daha sonra araştırmacılardan biri her çocukla görüşmeler yapmış ve Fleetham (2008) tarafından geliştirilen Çoklu Zeka Öz Değerlendirme Resim Kontrol Listesi’ni (MISEC) işaretlemelerini istemiştir. Toplanan veriler sınıfın Çoklu Zeka Profili’ni oluşturmak amacıyla grafikler haline dönüştürülüp yorumlanmıştır. İkinci aşamada, çocuklara, öğretmen liderliğinde, Çoklu Zeka Kuramı’ndan Esinlenilerek Zenginleştirilen Günlük Plan uygulanmıştır. Araştırmacılar sürecin tüm aşamalarını gözlemleyerek videoya kaydetmişlerdir. Daha sonra öğretmenin, Çoklu Zeka Kuramı’ndan esinlenilerek zenginleştirilen günlük planı, geleneksel günlük planlarıyla karşılaştırdığında çocukların ilgileri ve aktif katılımları konusunda farklılıklar olup olmadığı yönündeki görüşlerini öğrenmek amacıyla görüşmelere katılmıştır. Çalışmanın bulguları, Çoklu Zeka Kuramı’ndan Esinlenilerek Zenginleştirilen Günlük Plan’ın, tüm zeka türlerini kapsadığı ve çocukların farklı öğrenme stillerini ele aldığı için çocukların ilgi alanlarına ve günlük aktivitelere aktif katılımına olumlu yönde etki ettiğini göstermiştir. Araştırmanın sonuçları, Çoklu Zeka’nın okul öncesi dönem çocuklarının ilgileri ve aktif katılımları üzerindeki rolü hakkında fikir vermenin yanı sıra, sekiz zeka türünün tümünü kapsamanın ve günlük planlarda çocukların tüm öğrenme stillerini ele almanın önemine dikkat çekmektedir.
Çoklu Zeka Kuramı’nı Günlük Planlara Entegre Etme: Bir Anaokulu Örneği
Keywords: zeka; anaokulu; eğitim; öğrenme